Pedagogia de projetos na formação inicial de professores: possibilidade a partir da proposta Aprender Investigando - Andrade, Luciani Andrade de (2017)
This work results from research developed during de Professional Master Course in Technological Teaching, which aims to investigate if the Learning Investigating (LI) is a viable proposal of contribution to initial formation of teachers. It was supported epistemologically on concepts over teachers formation in Brazil, on pedagogy of projects, and over LI. The research occurred in a partnership with Biological Sciences and Chemical students of IFAM/ Manaus, Downtown Campus, through the discipline Pedagogical Practice 1 that was supported by the pedagogy of projects by applying The Learning Investigating Methodology, on which students made research during classes with investigative propositions from their experiences over the course. Considering the qualitative bias of research, it was realized the Participating Observation Technique to collect data, by the application of questionnaires, notes on field diaries, and analysis of text production resulting from activities performed by students during the discipline period, resulting in a testimonial of such experience that subsidized the educational product named Learning Investigating on Formation of Teachers Utilization Guide, that evidenced how to proceed on formation of teachers. Thus, hopefully research may contribute with new investigating proposals supported by new formative models, as this guide, wich is an instrument useful on teachers formation